How to respond to disruptive innovation in online retail platforms - Seojeong Yang; Yoonji Kim; Seungho Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This paper explores how the traditional incumbents coped with the rapid transition provoked by disruptive innovation in the South Korean retail industry. More specifically, the study concentrates on the challenges incumbents faced and their step-by-step attempts to deal with disruption. Shinsegae affiliates and SSG.COM were chosen as the target companies for our descriptive study. Shinsegae is one of the top three retail conglomerates in South Korea, owning various subsidiary brands. SSG.COM is also one of its subsidiaries, first established as the online distribution channel for Shinsegae affiliates. However, its role has later become expanded and critical, turning into an online marketplace aimed at overcoming disruption in the retail industry. By reviewing SSG.COM's dynamic responses to disruptive innovation, we found that what makes its incumbents vulnerable to sudden disruption lies in their static business model. Furthermore, the platform economy allowed offline retailers to be easily disrupted by the key characteristic of platform business - the "network effect". To counteract online market domination, this study implies that SSG.COM should innovate its business model to integrate its online and offline ecosystems successfully.
Keywords: 650; business model; disruptive innovation; incumbent response; online marketplace; platform business; retail; SSG.COM